Validation of a Novel Scoring System for Changes in Skeletal Manifestations of Hypophosphatasia in Newborns, Infants, and Children: The Radiographic Global Impression of Change Scale. (14th February 2018) - Whyte, Michael P; Fujita, Kenji P; Moseley, Scott; Thompson, David D; McAlister, William H
ABSTRACT: Hypophosphatasia (HPP) is the heritable metabolic disease characterized by impaired skeletal mineralization due to low activity of the tissue‐nonspecific isoenzyme of alkaline phosphatase. Although HPP during growth often manifests with distinctive radiographic skeletal features, no validated method was available to quantify them, including changes over time. We created the Radiographic Global Impression of Change (RGI‐C) scale to assess changes in the skeletal burden of pediatric HPP. Site‐specific pairs of radiographs of newborns, infants, and children with HPP from three clinical studies of asfotase alfa, an enzyme replacement therapy for HPP, were obtained at baseline and during treatment. Each pair was scored by three pediatric radiologists ("raters"), with nine raters across the three studies. Intrarater and interrater agreement was determined by weighted Kappa coefficients. Interrater reliability was assessed using intraclass correlation coefficients (ICCs) and by two‐way random effects analysis of variance (ANOVA) and a mixed‐model repeated measures ANOVA. Pearson correlation coefficients evaluated relationships of the RGI‐C to the Rickets Severity Scale (RSS), Pediatric Outcomes Data Collection Instrument Global Function Parent Normative Score, Childhood Health Assessment Questionnaire Disability Index, 6‐Minute Walk Test percent predicted, and Z ‐score for height in patients aged 6 to 12 years at baseline. Eighty‐nine percent (8/9) of raters showed substantial or almost perfect intrarater agreement of sequential RGI‐C scores (weighted Kappa coefficients, 0.72 to 0.93) and moderate or substantial interrater agreement (weighted Kappa coefficients, 0.53 to 0.71) in patients aged 0 to 12 years at baseline. Moderate‐to‐good interrater reliability was observed (ICC, 0.57 to 0.65). RGI‐C scores were significantly ( p ≤ 0.0065) correlated with the RSS and with measures of global function, disability, endurance, and growth in the patients aged 6 to 12 years at baseline. Thus, the RGI‐C is valid and reliable for detecting clinically important changes in skeletal manifestations of severe HPP in newborns, infants, and children, including during asfotase alfa treatment. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.